PELATIHAN PELAYANAN PELANGGAN BAGI PEGIAT ASURANSI DI P.T. MSIG INDONESIA, JAKARTA - Dian Anggraeny Rahim; Irma Citarayani; Dedi Damhudi; Sukardi Sukardi (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Customer service for a business institution is a must. For this reason, PT MSIG Indonesia, in collaboration with the Community Service Team of the Faculty of Economics, Darma Persada University, conducted a series of trainings to provide maximum customer service. The implementation of this service activity was carried out for two days and involved forty employees. The activity starts with gathering opinions related to employee needs. As many as 85.7% of employees agreed to hold training, and 14.3% proposed holding a gathering. For the majority vote, the activities carried out are training for employees. Then, the activity continued with focus group discussion (FGD) and made employee self-development strategies as an insurance activist. There are five important elements for increasing customer satisfaction, namely reliability, which is to make customers believe in the ability of insurance activists. The second is assurance namely, insurance activists must be able to explain the achievements achieved by the company and convey them to customers. The third is tangible, which can provide concrete and valuable services. Fourth is empathy, which can understand customer conditions, and responsiveness, responsible for all customer problems. These five attitudes are the basis for employees to act and behave in dealing with customers